2017
DOI: 10.18869/acadpub.ijop.11.2.123
|View full text |Cite
|
Sign up to set email alerts
|

Optical Opacity of Laser Induced Plasma in Distilled Water with NaCl and TiO2 Nanoparticles Impurities

Abstract: ABSTRACT-In this paper, the dynamic behavior of laser induced optical breakdown in impure water was studied by using a pumpprobe technique. The plasma was induced by a 1064 nm Nd:YAG laser pulse (with pulse duration ~10 ns) in distilled water with two types of impurities: (I) a solution (highly diluted salt water as a conductor) and (II) a colloidal (TiO 2 in colloidal nanoparticle form as a dielectric); and finally the results were compared. The results show that, for both liquids, the probe beam transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
0
1
Order By: Relevance
“…38 Another possible reason for this fact is that with the increase of impurities in water due to the excess of particles from NaCl, the free electrons coming from these impurities can reduce the laser fluence value necessary to achieve the breakdown, besides interfering with the transmissivity and the evolution of plasma in water. 39 Li et al 24 and Goueguel et al 26 observed an opposite effect to that presented in this work since the intensity of the emission lines for Ca I 422.7 nm and K I 769.5 nm increased simultaneously with the increase in NaCl concentration. This difference may be related to instrumental issues such as laser irradiance, laser transmission distance in water and different optical elements present in each experimental setup.…”
Section: Resultscontrasting
confidence: 75%
“…38 Another possible reason for this fact is that with the increase of impurities in water due to the excess of particles from NaCl, the free electrons coming from these impurities can reduce the laser fluence value necessary to achieve the breakdown, besides interfering with the transmissivity and the evolution of plasma in water. 39 Li et al 24 and Goueguel et al 26 observed an opposite effect to that presented in this work since the intensity of the emission lines for Ca I 422.7 nm and K I 769.5 nm increased simultaneously with the increase in NaCl concentration. This difference may be related to instrumental issues such as laser irradiance, laser transmission distance in water and different optical elements present in each experimental setup.…”
Section: Resultscontrasting
confidence: 75%